2021
DOI: 10.3390/nano11020527
|View full text |Cite
|
Sign up to set email alerts
|

Full-Scale Pore Structure Characteristics and the Main Controlling Factors of Mesoproterozoic Xiamaling Shale in Zhangjiakou, Hebei, China

Abstract: Nanoscale pore structure characteristics and their main controlling factors are key elements affecting the gas storage capacity, permeability, and the accumulation mechanism of shale. A multidisciplinary analytical program was applied to quantify the pore structure of all sizes of Xiamaling shale from Zhangjiakou, Hebei. The result implies that Mercury injection porosimetry (MIP) and low-pressure N2 curves of the samples can be divided into three and four types, respectively, reflecting different connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Pore networks within shales range from simple to complex in morphology, abundance, and origin, with most pores being less than several microns. Several publications have provided quantitative data and excellent images of shale or mudstones pores acquired by LPGA, MIP, NMR, and SEM petrographic evidence [ 8 , 9 , 14 , 15 , 16 , 17 , 18 ]. On the basis of the classifications of the International Union of Pure and Applied Chemistry (IUPAC), the pores that were obtained fell into three classes: micropores (pore width < 2 nm), mesopores (pore width between 2 and 50 nm), and macropores (pore width > 50 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pore networks within shales range from simple to complex in morphology, abundance, and origin, with most pores being less than several microns. Several publications have provided quantitative data and excellent images of shale or mudstones pores acquired by LPGA, MIP, NMR, and SEM petrographic evidence [ 8 , 9 , 14 , 15 , 16 , 17 , 18 ]. On the basis of the classifications of the International Union of Pure and Applied Chemistry (IUPAC), the pores that were obtained fell into three classes: micropores (pore width < 2 nm), mesopores (pore width between 2 and 50 nm), and macropores (pore width > 50 nm).…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent shale gas explorations in the Sichuan Basin, Xichang Basin, and Yanyuan Basin in Sichuan province from a total of 11 organic-rich shale formations in 2022 have technically recoverable reserves at 9 Tcf (trillion cubic feet), with economically recoverable-reserves of 5 Tcf. A great deal of research has been significantly reported in the literature about petrology, mineralogy, organic geochemistry, reservoir quality, generation potential, petrophysical properties, and microstructures in low-porosity and low-permeability shales [ 2 , 3 , 4 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The pore system preserved in fine grain, organic-rich shale can be used to identify gas storage space and migration pathways and estimate the total gas resources, thus serving as a distinct signature of predicting how hydrocarbon molecule are adsorbed and how transport takes place in such porous medium because the morphology, size, continuity, and occurrence medium of the pores can provide insights [ 4 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are three main methods of pore splicing, as follows: 1) From experience, three splicing points-25, 50, and 100 nm-are widely applied (Zhang et al, 2017;Xu et al, 2021); 2) According to the PSD image, the intersection of two curves or the midpoint of their parallel segments is usually selected for the splicing location (Xu et al, 2018); 3) The splicing point can be determined from an NMR T 2 curve (Xiao et al, 2020;Zheng et al, 2019a). The problems with these methods are also obvious: For method 1, the splicing points are frequently chosen based on the splicing findings of similar lithologies or study areas, making the points chosen highly subjective.…”
Section: Introductionmentioning
confidence: 99%
“…In the presented Special Issue, six research papers [ 1 , 2 , 3 , 4 , 5 , 6 ] are published. Topics of published papers cover analyses of different engineering problems of nanostructures.…”
mentioning
confidence: 99%